Regional variations in healthcare in people living with dementia in Germany: protocol for a mixed-methods study - Scheibner, Hannah Julia; Gesell, Daniela; Hauptmann, Michael; Heinze, Martin; Horenkamp-Sonntag, Dirk; Koller, Daniela; Kubat, Denise; Marschall, Ursula; Meixner, Johannes; Michalowsky, Bernhard; von Peter, Sebastian; Platen, Moritz; et al. (BMJ open, 2025)
IntroductionCare for people living with dementia is both important and complex, and there is evidence of large regional variations in the quality of care. This study protocol describes design, methods and objectives of an investigation of regional variations in the utilisation, the quality and the costs of care for people living with dementia in Germany.Methods and analysisAn exploratory, naturalistic, mixed-methods study is being conducted with three modules: Module A: A quantitative analysis of claims data of statutory health insurance will be conducted to investigate regional variations in the utilisation and costs of care. Module B: In selected regions of interest that deviate significantly from the average in terms of utilisation in Module A, the quality of care and patient characteristics, variations and possible causes of these variations in care will be examined in more detail using quantitative and qualitative assessments. Module C: The claims and primary data from modules A and B will be combined, synthesised and evaluated to elicit recommendations for regional healthcare using a participatory consensus method.Ethics and disseminationThe study is overseen by the German Alzheimer’s Association. The study’s ethics and data protection plan was approved by the data and ethics committee of the leading university, Brandenburg Medical School Theodor Fontane (reference number: 152092023-BO-E) as well as the data committee of the three participating health insurances. Dissemination plans include dissemination of our main results to the general public, people affected, the scientific community and funding-, policy- and decision makers. Study outcomes and conclusions will be published on our own and the funder’s websites, through presentations at conferences and in scientific journals. The funder ensures dissemination of main study results and recommendations for action to relevant organisations and institutions. Publication of the study’s main results is planned within 6 months of the study’s conclusion.Trial registration numberDRKS00031944 (https://trialsearch.who.int/Trial2.aspx?TrialID=DRKS00031944).